Atheletes get pocket money - The Malay Mail, Reena Raj (2007)
More than 130 Federal Territory athletes, who will be representing Malaysia in next month's 2007 Sea Games in Korat, Thailand, will have additional pocket money during the games, thanks to the Federal Territories Ministry.